Kepekaan Beberapa Populasi Plutella Xylostella Di Jawa Tengah Dan Yogyakarta Terhadap Bacillus Thuringiensis = The Susceptibility of Plutella xylostella Field Populations Collected from Central Java and Yogyakarta to Bac - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Abstract The research objective was to determine the susceptibility of nine field populations of the diamondback moth, Plutella xylostella L. collected from Central Java (Muntilan, Sawangan, Pakis, Sumowono, Ambarawa, Kopeng, dan Cepogo) and Yogyakarta (Turi and Pakem) to Bacillus thuringiensis. Caisim leaf disks were dipped for 10 s in B. thuringiensis solutions or control solution (water), and air dried. Ten second instars (four-d old) of P. xylostella were exposed on the treated or control leaf disks and placed in plastic cups (diameter 3 cm) for 48 h. Larval mortality was recorded at 48 h after exposure, and the surviving larvae were transfered to fresh control leaf disks. Larval mortality was then assessed one d after transfer (72 h after treatment). The LC^ values at 48 and 72 h after treatment varied from 230 to 44.57 mg/1 and 1.03 to 15.47 mg/1, respectively. Population of P. xylostella collected from Ambarawa was at least 15.0 times less susceptible than was Muntilan. However, all of these populations were susceptible to B. thuringiensis because their LC50 values were below the field aplication rate of B. thuringiensis for P. xylostella (2 g/1).